“Futuro. Qual é o seu?” Um estudo sobre a relação ensino médio X PEIES a partir da fala docente em Santa Maria/RS - Missio, Luciani (2007)
This work presents a study on the relation High School versus PEIES - Program of Ingression to University of the Federal University of Saint Mary - UFSM, from speaks of professors of the city of Mary Saint. By means of this study, it was looked to promote a reflection on the examinations of admission for ingression in University and the relation that had established, and still establish, in the practical teacher in the schools of High School in Brazil, special form examination PEIES, and in Mary Saint. This reflection was made through the agreement of program PEIES, the legislation that regulate it, as well as of its ideal and objective. One searched, through a bibliographical revision, to understand the society of century XXI and the origin of the school, and to know the history of High School in Brazil through its legislation and of the data-collecting of the MEC. To understand this relation, interviews with teacher of the schools of average education of the city and with teacher of the university had been made. The used methodology, in set with the bibliographical revision and referring legislations to the programs of seriada evaluation and of High School, was Verbal History, in the modality of Thematic Verbal History. Seven teachers had been interviewed: five of the public and private schools and two doctors in education of the UFSM. The work is divided in five chapters: description of the used methodology and the collaborators of the research; analysis of the social context and the origin of the current school; the PEIES; High School; e, finally, the presentation and analysis of the carried through interviews.